The Effect of The Work Environment on Front Office Employees' Performance at The Pacific Palace Hotel Batam - Sagala, Rahel Natasya; Lubis, Arina Luthfini; ., Supardi (Jurnal Manajemen Pelayanan Hotel, 2023)
Moreover, the city of Batam is strategically located near two national borders, namely Singapore and Malaysia,this is a big opportunity in the tourism sector, especially in the world of hotels. This research aims to analyzewhether the work environment has an influence on the effectiveness of employee performance, especially inthe front office environment at the Pacific Palace Hotel Batam. The research method used is a quantitativeapproach with simple regression analysis techniques to assess the relationship between 2 variables, workenvironment variables (as independent variables) and employee performance (as dependent variables). Dataprocessing uses simple regression analysis which includes normality test, T test and F test, and R2 test usingSPSS statistical software. The results are valid. In the hypothesis test results, H1 is accepted, this can also beseen from the significance results in tcount which has a result of 0.01. Overall the research results show thatthe hopethesis test on the work environment as a variable (X) has a positive effect on employee performanceas a variable (Y) both partially and simultaneous. The result of the regression equation is Y = 21.098 + 0.752X.The coefficient of determination (R2) results were 74.6%, which means employee performance beinginfluenced by other variables outside of this research test. Therefore, it is important for hotel management toprioritize improving working environment conditions, including employee training and development, so thatmaintaining employee welfare through the work environment can improve employee performance resultswhich ultimately can maintain competitiveness in the competitive hospitality industry.